Variations in the Phagosomal Environment of Human Neutrophils and Mononuclear Phagocyte Subsets - Foote, Juliet R.; Patel, Amit A.; Yona, Simon; Segal, Anthony W. (Frontiers in Immunology, 2019)
The phagosome microenvironment maintains enzyme activity and function. Here we compared the phagosomal pH of human neutrophils, monocytes, dendritic cells (DC) and monocyte-derived cells. An unexpected observation was the striking difference in phagosomal environment between the three monocytes subsets. Classical monocytes and neutrophils exhibited alkaline phagosomes, yet non-classical monocytes had more acidic phagosomes, while intermediate monocytes had a phenotype in-between. We next investigated the differences between primary naïve DC versus in vitro monocyte-derived DC (MoDC) and established that both these cells had acidic phagosomal environments. Across all phagocytes, alkalinisation was dependent upon the activity of the NADPH oxidase activity, demonstrated by the absence of NADPH oxidase from a patient with chronic granulomatous disease (CGD) or the use of a pharmacological inhibitor, diphenylene iodonium (DPI). Interestingly, MoDC stimulated with bacterial lipopolysaccharide had increased phagosomal pH. Overall, the increase in alkalinity within the phagosome was associated with increased oxidase activity. These data highlight the heterogeneous nature and potential function of phagocytic vacuoles within the family of mononuclear phagocytes.